THE NO SINUSOIDAL VOLTAGES UNDER THE SINUSOIDAL CURRENT AT THE ENTRY OF THE OPEN–ENDED LINE WITH REAL LOSS - Patsiuk V.I. (Problems of the Regional Energetics, 2008)
he classical problems of the theoretical electrical engineering, such as open-ended (or short-circuited) line energization on alternating voltage (or current), are solved by means of Fourier series method. The conditions of creation of no sinusoidal steady-state regimes in the lines with nonzero loss are discovered.